2019
DOI: 10.1177/2396987319845578
|View full text |Cite
|
Sign up to set email alerts
|

E-Poster Discussions

Abstract: Background and aims: It remains unclear whether patients presenting with large vessel occlusion strokes and mild symptoms benefit from mechanical thrombectomy (MT). The purpose of the present study was to compare outcomes in acute ischemic stroke patients with intracranial vessel occlusions and minor stroke symptoms (NIHSS 5 or lower) treated with MTwith those who treated with intravenous thrombolysis (IVT) alone. Methods: In a prospective observational study at Oslo University Hospital, we assessed the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…HT extent may range from single-blood petechiae with few clinical consequences to symptomatic HT with a high rate of mortality and disability. While most studies reported the association between BBB disruption and HT, only few studies investigated the relation with unfavorable outcomes such as symptomatic intracranial hemorrhage (sICH) (20,26,34); therefore, this association, although potentially useful for clinicians, is still unclear and needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HT extent may range from single-blood petechiae with few clinical consequences to symptomatic HT with a high rate of mortality and disability. While most studies reported the association between BBB disruption and HT, only few studies investigated the relation with unfavorable outcomes such as symptomatic intracranial hemorrhage (sICH) (20,26,34); therefore, this association, although potentially useful for clinicians, is still unclear and needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, we extracted from the studies mean age of patients, stroke severity, site of occlusion, and time from onset to enrolment, and we observed that particularly in CT studies, such variables were similar, whereas in MR studies, there was more difference. It should be noted that only 4/14 CT studies (15,23,24,26) and 10/16 MR studies (27-30, 32, 34-36, 42) reported univariate associations between BBB disruption and HT and were included in the meta-analysis; consequently, the ORs were found to represent a gross estimate of the relation between BBB and HT and should be interpreted with caution. Many CT and MR studies reported only adjusted associations; however, the sets of covariates largely differed across studies; thus, pooling-adjusted ORs were potentially inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations